Cemetery kids don't die. 1 - Thompson, Zac (Oni Press, 2024)
"The twenty-first century sucks hard, but it's been made somewhat tolerable by the latest media innovation to finally unseat the iPhone. Enter the Dreamwave: the first gaming console played entirely while you sleep. Now the obsession of millions around the globe, it's also the one point of solace for four friends whose lives have been marred by trauma and dysfunction. Together, this group of ultra-online "Cemetery Kids" spend their nights roaming the open world of the most immersive and brutal horror game ever created: "Nightmare Cemetery." Together they seek to dethrone an enigmatic humanoid monster known only as the "The King of Sleep." Which was fun--until one of them doesn't wake up... and finds their consciousness locked inside a horror game that is anything but imaginary. Now, the three remaining Cemetery Kids must navigate the game's forbidden landscape to rescue their friend... and pray that the secret lurking at its center doesn't follow them home"--